2017
DOI: 10.1063/1.4975163
|View full text |Cite
|
Sign up to set email alerts
|

2D lattice model of a lipid bilayer: Microscopic derivation and thermodynamic exploration

Abstract: Based on all-atom Molecular Dynamics (MD) simulations of a lipid bilayer we present a systematic mapping on a 2D lattice model. Keeping the lipid type and the chain order parameter as key variables we derive a free energy functional, containing the enthalpic interaction of adjacent lipids as well as the tail entropy. The functional form of both functions is explicitly determined for saturated and polyunsaturated lipids. By studying the lattice model via Monte Carlo simulations it is possible to reproduce the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…A comparison of the MD and MC simulations revealed a qualitative agreement with respect to the unmixing process (upper and middle frames). Such an agreement was even found on a quantitative level (Hakobyan and Heuer 2017 ). Importantly, the MC simulations were eight orders of magnitude faster than the MD simulations.…”
Section: Simplified Models Of Lipid Membranes and Their Componentssupporting
confidence: 57%
See 2 more Smart Citations
“…A comparison of the MD and MC simulations revealed a qualitative agreement with respect to the unmixing process (upper and middle frames). Such an agreement was even found on a quantitative level (Hakobyan and Heuer 2017 ). Importantly, the MC simulations were eight orders of magnitude faster than the MD simulations.…”
Section: Simplified Models Of Lipid Membranes and Their Componentssupporting
confidence: 57%
“…Later on, it could be shown that with time-consuming MD simulations the onset of the domain formation could also be obtained from united atom modelling, which required simulation times of more than 10 μs (Hakobyan and Heuer 2013 ). A recently introduced 2D-lattice-based approach was used to exceed the previous limitations in timescale and length scale by orders of magnitude (Hakobyan and Heuer 2017 ). At the same time, it allowed the extraction of the underlying information about the thermodynamic origin of domain formation.…”
Section: Simplified Models Of Lipid Membranes and Their Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of significant dependence on cholesterol concentration, the impact of the PL-interaction with water and the opposite leaflet can be directly taken into account by the use of an effective entropy function, as used, e.g., in. 41 This model may help to better rationalize the impact of local interaction properties on the mesoscopic phase behavior of lipid mixtures. Figure S4: Interleaflet interaction as a function of both, the lipids overlap and its chain order parameter in respective bilayer DPPC/CHOL and DLiPC/CHOL mixtures from 0% to 30% CHOL.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of nearest neighbor interactions to describe the lateral range of influence has been discussed in various simplistic models of lipid bilayers, strongly supporting the notion that lipids in a bilayer are only influenced by their nearest neighbors. [41][42][43] The question arises whether this influence or lack thereof can effectively be observed in the interaction functions and how this observation deviates between the examined lipid types.…”
Section: Implications For Bilayer Modelsmentioning
confidence: 99%